[pex'dida] ou [pex'd3ida]?, [tc'matr] ou [tc'matfI]?:uma análise geossociolinguística da realização dos fonemas /d/ e /t/ no falar de ararienses e pinheirenses - DUTRA, Francimone da Graça Barros (2021)
The origin of this dissertation is ruled as in our knowledge about the popularly rumored depalatalized realization of the phonemes /d/ and /t/ before [i I] in some cities from Baixada Maranhense – that would historically particularize the speak of this region related to the other ones –, as in our perception, based in the experience, that we have in Arari City, from differences existing in the speak of people from Maranhão State who lives is some cities of this microregion and from people who were born in other parts of this State. It was added to this the knowledge from important studies about the Portuguese spoken In Maranhão developed, mainly, by Atlas Linguístico do Maranhão – ALiMA. We decided to investigate the speak from people who were born in the cities of Arari and Pinheiro, whose represent the microregion called as Baixada Maranhense in this study. So, the main aim of this research is to investigate, according to the Dialectology, Geolinguistics and Sociolinguistics, the realization of the phonemes /d/ and /t/ before of [i I] in the cities of Arari and Pinheiro, aiming to confirm or refuting the depalatalized realization of these phonemes in Baixada Maranhense. As specific objectives, we establish: i) identifying the linguistcs and extralinguistics facts responsible for the realization of the /d/ e /t/ phonemes before of [i I] in the localities investigated, based on the the Goldvarb X computer program (GUY; ZILLES, 2007); ii) analyzing the linguistic and extralinguistic relevant variables to the depatalized or palatalized realization of these phonemes in the investigated contexts, in order to contribute to the descriptive systematization of the contemporary Baixada Maranhense´s speak, represented in this study by the cities of Arari and Pinheiro. Therefore, we were theoretically grounded in the Phonetic and Phonology studies developed by Saussure (1916), Roberto (2016), Silva (2017), Seara, Nunes, Lazzarotto-Volcão (2019); about the depalatalization and palatalization realized by Cagliari (1974), Bergo (1986), Battisti et. al. (2007), Ilari & Basso (2007), Araújo (2011) and Aragão (2018); about Dialectology and Geolinguistics developed, mainly, by Rossi (1980), Aguilera (2006), Cardoso (2010), Romano (2013); and about Sociolinguistics realized by Labov (1972), Tarallo (1986), Bortoni-Ricardo (2004), Monteiro (2008), Mollica & Braga (2015), Guy & Zilles (2007). According to this theoretical basis, this investigation was methodologically organized in three main steps: i) contextualization of the field of research; ii) locus of this research; and iii) constitution and treatment of the data – data from Pinheiro City colected by the ALiMA Project and the data from Arari City colected by the author of this work. In general, the obtained results contradicted the claimed depalatalized realization of the /d/ and /t/ phonemes before of [i I] in Baixada Maranhense. This way, we hope that this work contributes to incentivate the deepening of the studies about the variety of the Brazilian Portuguese spoken in Maranhão, more specifically, the ampliation of the investigation about the realization of the /d/ and /t/ phonemes before of [i I], that, consequently, contributes to the recognition and valorization of the linguistic diversity from the State and from the country.